(untitled) (Czech Journal of International Relations, 2002)
International Workshop on the Czech Republic’s Accession to the European Union. 1st ed. Prague: Institute of Integration of the Czech Republic into the European and World Economy and University of Economics, 2001, 138 s., ISBN 80-245-0191-0.